Gestational Gigantomastia Complicating Pregnancy: A Case Report and Review of the Literature. (2nd December 2015) - Rezai, Shadi; Nakagawa, Jenna T.; Tedesco, John; Chadee, Annika; Gottimukkala, Sri; Mercado, Ray; Henderson, Cassandra E.
Abstract : Background . Gestational gigantomastia is a rare disorder without clear etiology or well-established risk factors. Several pathogenic mechanisms contributing to the disease process have been proposed, all of which can lead to a similar phenotype of breast hypertrophy. Case . A 28-year-old Guinean woman presented at 37 weeks of gestation with bilateral gigantomastia, mastalgia, peau d'orange, and back pain. Prolactin levels were 103.3  μ g/L (with a normal reference value for prolactin in pregnancy being 36–372  μ g/L). The patient was treated with bromocriptine (2.5 mg twice daily), scheduled for a repeat cesarean, and referred to surgery for bilateral mammoplasty. Conclusion . Gestational gigantomastia is a rare disorder, characterized by enlargement and hypertrophy of breast tissue. Our patient presented with no endocrine or hematological abnormalities, adding to a review of the literature for differential diagnoses, workup, and management of cases of gestational gigantomastia with normal hormone levels.